Electrolytic capacitor and method of manufacturing the same

CN117157723BActive Publication Date: 2026-10-27PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202280027928.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-15
Filing Date
2022-04-12
Publication Date
2026-10-27
Estimated Expiration
2042-04-12

AI Technical Summary

Benefits of technology

[0012]根据本发明,能够降低电解电容器的ESR。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117157723B_ABST
    Figure CN117157723B_ABST
Patent Text Reader

Abstract

An electrolytic capacitor includes: an anode body; a dielectric layer covering the anode body; a first solid electrolyte layer covering the dielectric layer; and a second solid electrolyte layer covering the first solid electrolyte layer. The first solid electrolyte layer contains a first conductive polymer having a polythiophene as a basic skeleton, and the second solid electrolyte layer contains a second conductive polymer having a polypyrrole as a basic skeleton. The first solid electrolyte layer has an electric conductivity of 2 S / cm or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrolytic capacitor and a method for manufacturing the same. Background Technology

[0002] An electrolytic capacitor includes a capacitor element comprising an anode, a dielectric layer covering the anode, and a solid electrolyte layer covering the dielectric layer. The solid electrolyte layer comprises a conductive polymer, such as polypyrrole (e.g., Patent Document 1).

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent Application Publication No. 2008-118060 Summary of the Invention

[0006] The problem the invention aims to solve

[0007] For electrolytic capacitors, a reduction in ESR (equivalent series resistance) is required.

[0008] Solution for solving the problem

[0009] One aspect of the present invention relates to an electrolytic capacitor comprising: an anode body, a dielectric layer covering the anode body, a first solid electrolyte layer covering the dielectric layer, and a second solid electrolyte layer covering the first solid electrolyte layer, the first solid electrolyte layer comprising a first conductive polymer with polythiophene as a basic backbone, the second solid electrolyte layer comprising a second conductive polymer with polypyrrole as a basic backbone, and the conductivity of the first solid electrolyte layer being less than 2 S / cm.

[0010] Another aspect of the present invention relates to a method for manufacturing an electrolytic capacitor, comprising: a first step of preparing an anode body having a dielectric layer formed thereon; a second step of forming a first solid electrolyte layer comprising a first conductive polymer with a polythiophene as a basic backbone on the dielectric layer; and a third step of electrolytically polymerizing a precursor of a second conductive polymer with a polypyrrole as a basic backbone on the first solid electrolyte layer to form a second solid electrolyte layer comprising the second conductive polymer, wherein the conductivity of the first solid electrolyte layer is less than 2 S / cm.

[0011] The effects of the invention

[0012] According to the present invention, the ESR of electrolytic capacitors can be reduced.

[0013] Although novel features of the invention are described in the appended claims, the invention can be better understood through the following detailed description, which relates to both structure and content, and in conjunction with other objects and features of the invention and with reference to the accompanying drawings. Attached Figure Description

[0014] Figure 1 A cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention is shown schematically.

[0015] Figure 2 To illustrate Figure 1 Enlarged cross-sectional view of region II. Detailed Implementation

[0016] The following examples illustrate embodiments of the electrolytic capacitors disclosed herein, but the disclosure is not limited to the examples described below. In the following description, specific values ​​and materials are sometimes shown, but other values ​​and materials may be used as long as the effects of the disclosure are achieved. In this specification, the phrase "value A to value B" includes both value A and value B, and can be read as "value A or higher and value B or lower." In the following description, when lower and upper limits of values ​​related to specific physical properties, conditions, etc., are shown, any combination of any of the shown lower limits and any of the shown upper limits may be used, as long as the lower limit is not higher than the upper limit. When multiple materials are shown, one may be selected for use alone, or two or more may be combined.

[0017] Furthermore, this disclosure includes a combination of the contents of any two or more claims selected from the plurality of claims recited in the appended claims. In other words, the contents of any two or more claims selected from the plurality of claims recited in the appended claims can be combined, provided that no technical contradiction arises.

[0018] "Electrolytic capacitor" can also be read as "solid electrolytic capacitor", and "capacitor" can also be read as "capacitor".

[0019] One embodiment of the present invention relates to an electrolytic capacitor comprising: an anode body, a dielectric layer covering the anode body, a first solid electrolyte layer covering the dielectric layer, and a second solid electrolyte layer covering the first solid electrolyte layer. The first solid electrolyte layer (hereinafter also referred to as the first layer) comprises a first conductive polymer (hereinafter also referred to as a polythiophene-based polymer) with a polythiophene-based backbone and has a conductivity of 2 S / cm or less. The second solid electrolyte layer (hereinafter also referred to as the second layer) comprises a second conductive polymer (hereinafter also referred to as a polypyrrole-based polymer) with a polypyrrole-based backbone.

[0020] The second layer, comprising a polypyrrole polymer, is formed by electrolytic polymerization of a polypyrrole polymer precursor on a dielectric layer formed on the surface of an anode body, after a conductive first layer is formed on the first layer. The first layer functions as an electrode during electrolytic polymerization. A well-formed second layer is achieved through electrolytic polymerization. The inventors have conducted in-depth research on the first layer. As a result, they have discovered that when the first layer comprises a polythiophene polymer and has a conductivity of 2 S / cm or less, the ESR of the electrolytic capacitor having a second layer comprising a polypyrrole polymer is reduced.

[0021] When the first layer contains a polythiophene polymer and has a conductivity of less than 2 S / cm, an exceptionally low ESR can be obtained in an electrolytic capacitor with a second layer containing a polypyrrole polymer. Although the specific reasons are not yet clear, the following factors can be speculated as the main reasons for the low ESR.

[0022] Sometimes, crystallization or cracks in a portion of the dielectric layer can cause a short circuit, allowing high current to flow. In this case, some conductive polymers will typically become insulating due to the high current, thus suppressing the short circuit. On the other hand, this insulation increases the resistance of the solid electrolyte layer, leading to an increase in ESR.

[0023] In contrast, in this invention, the conductivity of the first layer is as low as 2 S / cm, making it easy to insulate. Insulation of the first layer suppresses insulation of the second layer. Furthermore, since the first layer is used as an electrode during electrolytic polymerization, it is formed to be sufficiently thinner than the second layer. By locally insulating the thin first layer, the impact of insulation on the overall solid electrolyte layer can be reduced. Therefore, the resistance of the second layer can be maintained at a low level, suppressing the rise in ESR.

[0024] It is predicted that degradation of the first layer can easily affect ESR. However, by using a polythiophene-based polymer film with excellent thermal stability and durability as the first layer, the increase in ESR caused by the degradation of the first layer can be suppressed. Furthermore, compared to cases where the first layer is a polypyrrole-based or polyaniline-based polymer film formed through chemical polymerization, the energy level (work function) difference between a polythiophene-based polymer film and a polypyrrole-based polymer film formed through electrolytic polymerization (the second layer) is smaller. This is also speculated to be one of the main reasons for the lower ESR.

[0025] From the perspective of reducing ESR, the conductivity of the first layer is preferably 0.1 S / cm or more and 2 S / cm or less, more preferably 0.1 S / cm or more and 1 S / cm or less, and even more preferably 0.1 S / cm or more and 0.5 S / cm or less. When the conductivity of the first layer is 0.1 S / cm or more, it is easier to suppress capacity reduction.

[0026] The conductivity of the first layer can be determined using the following method.

[0027] The electrolytic capacitor is disassembled, the capacitor element is removed, and the composition of the first layer is analyzed. The first processing solution can also be analyzed when forming the first layer using the first processing solution in the second step described later. Analytical methods include TEM (transmission electron microscopy)-EELS (electron energy loss spectroscopy), NMR (nuclear magnetic resonance spectroscopy), and Raman spectroscopy.

[0028] Based on the analytical results, a sample film containing the same components as the first layer (e.g., thickness 20 μm to 40 μm) is formed, and the conductivity of this sample film is determined as the conductivity of the first layer. The sample film can be formed by preparing a sample solution (aqueous solution) containing the same components as the first layer (e.g., a self-doped polythiophene polymer), coating the sample solution onto a substrate, and allowing it to dry. Alternatively, a first processing solution can be used to form the sample film. As the apparatus for measuring conductivity, the Loresta-GX and PSP probes manufactured by Nitto Seiko Analytical Technology Co., Ltd. can be used.

[0029] The first layer has low electrical conductivity. By forming a thin first layer, the increase in ESR can be suppressed. From the perspective of reducing ESR, the thickness T1 of the first layer is preferably 10 nm or less, more preferably 5 nm or less. The lower limit of the thickness T1 of the first layer is, for example, 1 nm.

[0030] It should be noted that the thickness T1 of the first layer refers to the thickness of the first layer covering the inner wall of the porous part of the anode body, separated by the dielectric layer. Figure 2 The thickness of the first layer (T1) can be determined as follows: First, disassemble the electrolytic capacitor, remove the capacitor element, and obtain an image of the cross-section of the capacitor element using a transmission electron microscope (TEM). Using this image, measure the thickness of the first layer at any 10 points covering the inner wall of the porous part. Calculate the average of these measured thickness values. It should be noted that the first and second layers can be confirmed, for example, by TEM-EDX (energy-dispersive X-ray spectroscopy) analysis (elemental mapping).

[0031] From the perspective of reducing ESR, the second layer is preferably thicker and has higher conductivity than the first layer. From the perspective of reducing ESR, the conductivity of the second layer can be 30 S / cm or higher, or 60 S / cm or higher. From the perspective of reducing leakage current, the conductivity of the second layer can be 300 S / cm or lower, or 150 S / cm or lower. The conductivity of the second layer can be any combination of the aforementioned upper and lower limits, for example, it can be 30 S / cm or higher and 300 S / cm or lower, 60 S / cm or higher and 300 S / cm or lower, or 30 S / cm or higher and 150 S / cm or lower.

[0032] The thickness T2 of the second layer can be greater than 50 nm, or greater than 50 nm but less than 100 nm. The ratio of the thickness T2 of the second layer to the thickness T1 of the first layer, i.e., T2 / T1, can be greater than 10. It should be noted that the thickness T2 of the second layer refers to the thickness of the second layer that covers the outer surface of the porous portion of the anode body, separated from the dielectric layer and the first layer (or dielectric layer). Figure 2 The thickness of the second layer (T2) can be determined using the same method as the thickness of the first layer.

[0033] The conductivity of the second layer can be determined using the same method as that of the first layer. Based on the analysis results, a sample film containing the same composition as the second layer (e.g., with a thickness of 20 μm to 40 μm) is formed, and the conductivity of this sample film is determined as the conductivity of the second layer.

[0034] The second layer is formed by electrolytic polymerization of a polypyrrole polymer precursor in the presence of a second dopant. Therefore, a sample film with the same composition as the second layer (polypyrrole polymer and the second dopant) can be formed by preparing a sample solution containing a polypyrrole polymer precursor and the second dopant, immersing a metal substrate in the sample solution, and then electrolytically polymerizing the precursor by passing an electric current through the metal substrate. Furthermore, when forming the second layer using the second processing solution in the third step described later, the second processing solution can be analyzed, and the sample film can also be formed using the second processing solution.

[0035] The following section provides a more detailed explanation of electrolytic capacitors and their manufacturing methods.

[0036] Electrolytic capacitors

[0037] (Anode)

[0038] The anode body can include valve-acting metals, alloys containing valve-acting metals, and compounds containing valve-acting metals. These materials can be used alone or in combination of two or more. For example, aluminum, tantalum, niobium, and titanium are preferred as valve-acting metals. The anode body can have a porous surface. Such an anode body is obtained, for example, by roughening the surface of a substrate (such as a foil or plate-like substrate) containing the valve-acting metal through etching or other methods. Alternatively, the anode body can also be a molded body or a sintered body of particles containing the valve-acting metal. The sintered body has a porous structure, therefore the entire anode body can be porous.

[0039] (Dielectric layer)

[0040] The dielectric layer is formed, for example, by chemically converting (anodic oxidation) an anode body containing a valve-acting metal. The dielectric layer is formed to cover at least a portion of the anode body. The dielectric layer is typically formed on the surface of the anode body. Alternatively, the dielectric layer may be formed on the surface of the porous portion of the anode body, along the outer surface of the porous portion and the inner wall of the pores (pits).

[0041] The dielectric layer contains an oxide of the valve-acting metal. For example, when tantalum is used as the valve-acting metal, the dielectric layer contains Ta₂O₅; when aluminum is used as the valve-acting metal, the dielectric layer contains Al₂O₃. However, the dielectric layer is not limited to these; it can be any material that functions as a dielectric.

[0042] (Solid electrolyte layer)

[0043] The solid electrolyte layer is formed in a manner that covers the dielectric layer. The solid electrolyte layer need not cover the entire dielectric layer (the entire surface), but only a portion thereof. The solid electrolyte layer contains a first layer comprising a polythiophene-based polymer and a second layer comprising a polypyrrole-based polymer formed on the first layer. If there are regions on the dielectric layer where the first layer is not formed, the second layer may also be formed on the dielectric layer in those regions.

[0044] (Level 1)

[0045] The first layer contains polythiophene polymers. Polythiophene polymers include polythiophene and its derivatives. Examples of polythiophene polymers include poly(3,4-ethylenedioxythiophene) (PEDOT).

[0046] From the perspective of facilitating penetration into the pores of porous materials, the weight-average molecular weight of polythiophene polymers can be below 100,000 or below 30,000. For example, the weight-average molecular weight of polythiophene polymers is above 1,000. It should be noted that in this specification, the weight-average molecular weight refers to the weight-average molecular weight of polystyrene as determined by gel permeation chromatography (GPC).

[0047] The first layer can contain a self-doped polythiophene polymer with a conductivity of 2 S / cm or less. The particles of the self-doped polythiophene polymer are easily miniaturized. Therefore, in this case, a dispersion or solution of the polythiophene polymer can be easily prepared as the first processing liquid. Furthermore, the dispersion (solution) of the polythiophene polymer can easily penetrate into the pores of the porous portion.

[0048] It should be noted that self-doped polythiophene polymers refer to conductive polymers that possess anionic groups covalently bonded directly or indirectly to the polythiophene backbone of the conductive polymer. The anionic groups inherent in the conductive polymer itself act as dopants, hence the term "self-doped." These anionic groups may contain, for example, acidic groups (acidic form) or their conjugated anionic groups (salt form).

[0049] Examples of anionic groups in polythiophene polymers include sulfonic acid groups, carboxyl groups, phosphate groups, phosphonic acid groups, or their salts (salts with inorganic bases, salts with organic bases, etc.). Polythiophene polymers may have one or more anionic groups. Sulfonic acid groups or their salts are preferred as anionic groups, but combinations of sulfonic acid groups or their salts with anionic groups other than sulfonic acid groups or their salts are also possible. Regarding the amount of anionic groups contained in a polythiophene polymer, for example, relative to each molecule corresponding to the main backbone of the polythiophene polymer, 1 to 3 groups are preferred, more preferably 1 or 2 (especially 1).

[0050] The first layer may contain a non-self-doped polythiophene polymer or a first dopant. The first layer may also contain a polythiophene polymer composite with a conductivity below 2 S / cm, consisting of the polythiophene polymer and the first dopant. In the first layer, the first dopant may be present in anionic form or in salt form.

[0051] As a non-self-doped polythiophene polymer, examples include conductive polymers that do not have anionic groups (specifically sulfonic acid groups, carboxyl groups, phosphate groups, phosphonic acid groups, and their salts) directly or indirectly bonded by covalent bonds to the polythiophene backbone of the conductive polymer.

[0052] As the first dopant, a dopant capable of forming polyanions can be used, for example. Examples of first dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylamide sulfonic acid, and polymethacrylamide sulfonic acid.

[0053] The first layer may contain conductive polymers other than polythiophene polymers, but preferably contains a higher proportion of polythiophene polymers. The proportion of polythiophene polymers in the total conductive polymers contained in the first layer is, for example, 90% by mass or more, or even 100% by mass.

[0054] The first layer can be a single layer or composed of multiple layers. If the first layer is composed of multiple layers, the polythiophene polymer contained in each layer can be the same or different. The first layer may further contain other components without impairing the effects of the present invention.

[0055] (Level 2)

[0056] The second layer contains polypyrrole polymers. Polypyrrole polymers include polypyrrole and its derivatives. The weight-average molecular weight of polypyrrole polymers is not particularly limited, for example, it is above 1,000 and below 1,000,000.

[0057] The second layer can contain a non-self-doped polypyrrole polymer or a second dopant. It should be noted that a non-self-doped polypyrrole polymer can be, for example, a conductive polymer that does not have anionic groups (specifically sulfonic acid groups, carboxyl groups, phosphate groups, phosphonic acid groups, and their salts) directly or indirectly covalently bonded to the polypyrrole backbone of the conductive polymer.

[0058] As a second dopant, dopants capable of forming anions can be used, for example. Examples of second dopants include sulfuric acid, nitric acid, phosphoric acid, boric acid, and organic sulfonic acids. Examples of organic sulfonic acids include aromatic sulfonic acids. Examples of aromatic sulfonic acids include benzenesulfonic acid, alkylbenzenesulfonic acid, naphthalenesulfonic acid, and alkylnaphthalenesulfonic acid.

[0059] In the second layer, the second dopant can also form a polypyrrole polymer complex with the polypyrrole polymer. In the second layer, the second dopant can be contained in anionic form or in salt form.

[0060] The second layer may contain conductive polymers other than polypyrrole polymers, but preferably contains a higher proportion of polypyrrole polymers. The proportion of polypyrrole polymers in the total conductive polymer content of the second layer is, for example, 90% by mass or more, or even 100% by mass.

[0061] The second layer can be a single layer or composed of multiple layers. If the second layer is composed of multiple layers, the polypyrrole polymer contained in each layer can be the same or different. The second layer may further contain other components without impairing the effects of the present invention.

[0062] Figure 1 A cross-sectional view illustrating the structure of an electrolytic capacitor according to one embodiment of the present invention is shown for illustrative purposes. Figure 2 For illustrative purposes only Figure 1An enlarged cross-sectional view of region II. The electrolytic capacitor 1 includes: a capacitor element 2, a resin sealing material (outer casing) 3 for sealing the capacitor element 2, and an anode terminal 4 and a cathode terminal 5, each at least partially exposed to the outside of the resin sealing material 3. The anode terminal 4 and the cathode terminal 5 may be made of metal (copper or copper alloy, etc.). The resin sealing material 3 has a generally cuboid shape, and the electrolytic capacitor 1 also has a generally cuboid shape. Epoxy resin may be used as a raw material for the resin sealing material 3, for example.

[0063] The capacitor element 2 includes: an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. The cathode portion 8 includes: a solid electrolyte layer 9 covering the dielectric layer 7, and a cathode lead-out layer 10 covering the solid electrolyte layer 9. The cathode lead-out layer 10 has a carbon layer 11 and a silver paste layer 12.

[0064] The anode body 6 has a porous portion 6a and includes a region opposite to the cathode portion 8 and a region not opposite to it. The porous portion 6a contains a plurality of pores P. The pores P can be sponge-like pits or tunnel-like pits. In the portion of the anode body 6 not opposite to the cathode portion 8 adjacent to it, an insulating separation layer 13 is formed in a strip-like manner covering the surface of the anode body 6 to restrict contact between the cathode portion 8 and the anode body 6. Another portion of the anode body 6 not opposite to the cathode portion 8 is electrically connected to the anode terminal 4 by welding. The cathode terminal 5 is electrically connected to the cathode portion 8 by an adhesive layer 14 formed of a conductive adhesive.

[0065] The main surfaces 4S and 5S of the anode terminal 4 and the cathode terminal 5 are exposed from the same side of the resin sealing material 3. This exposed surface is used for welding to a substrate (not shown) on which the electrolytic capacitor 1 should be mounted.

[0066] The carbon layer 11 only needs to be conductive; for example, it can be constructed using a conductive carbon material (graphite, etc.). As the silver paste layer 12, a composition containing silver powder and a binder resin (epoxy resin, etc.) can be used, for example. It should be noted that the structure of the cathode lead-out layer 10 is not limited to this; any structure with current-collecting function is acceptable.

[0067] The solid electrolyte layer 9 is formed in a manner that covers the dielectric layer 7. The dielectric layer 7 is formed along the surface of the anode body 6 (the outer surface S of the porous portion 6a and the inner wall surface of the pore P). The surface of the dielectric layer 7 is formed with an uneven shape corresponding to the shape of the surface of the anode body 6. The solid electrolyte layer 9 is preferably formed in a manner that fills such unevenness in the dielectric layer 7.

[0068] The solid electrolyte layer 9 comprises a first layer 9a and a second layer 9b. The first layer 9a is formed such that it covers the outer surface S of the porous portion 6a and the inner wall surface of the pore P through the dielectric layer 7. The second layer 9b is formed such that it covers the outer surface S of the porous portion 6a through the dielectric layer 7 and the first layer 9a. Additionally, the second layer 9b is also formed within the pore P of the porous portion 6a, covering the inner wall surface of the pore P through the dielectric layer 7 and the first layer 9a. The first layer 9a contains a polythiophene-based polymer, and the second layer 9b contains a polypyrrole-based polymer. The conductivity of the first layer 9a is 2 S / cm or less. The first layer 9a and the second layer 9b have thicknesses T1 and T2, respectively.

[0069] The electrolytic capacitor described in this embodiment is not limited to the aforementioned structure and can be applied to electrolytic capacitors of various structures. Specifically, the present invention can also be applied to wound electrolytic capacitors, electrolytic capacitors using a sintered body of metal powder as the anode body, etc. The anode body can be a porous body with a portion of the anode lead embedded therein, and the anode terminals and the anode lead can also be electrically connected.

[0070] [Manufacturing Method of Electrolytic Capacitors]

[0071] One embodiment of the present invention relates to a method for manufacturing an electrolytic capacitor, comprising: a first step of preparing an anode body having a dielectric layer formed thereon; a second step of forming a first layer on the dielectric layer; and a third step of forming a second layer on the first layer. The first layer comprises a polythiophene-based polymer, and the second layer comprises a polypyrrole-based polymer. Furthermore, the conductivity of the first layer is 2 S / cm or less. Through the second and third steps, a solid electrolyte layer having the first and second layers is formed. Additionally, the method for manufacturing the electrolytic capacitor may include a step of preparing the anode body prior to the first step. The manufacturing method may also include a step of forming a cathode lead-out layer and / or a step of sealing the capacitor element.

[0072] The following is a more detailed explanation of each process.

[0073] (Process for preparing the anode)

[0074] In this process, the anode body is formed using known methods, depending on the type of anode body.

[0075] The anode body can be prepared, for example, by roughening the surface of a foil-like or plate-like substrate containing the valve-acting metal. Surface roughening creates a porous layer on the surface of the anode body. As for surface roughening, any method that creates unevenness on the substrate surface is acceptable; for example, it can be performed by etching (e.g., electrolytic etching) the substrate surface.

[0076] Alternatively, by preparing powder of a valve-acting metal (e.g., tantalum) and embedding one end of a rod-shaped anode lead along its length in the powder, a molded body of the desired shape (e.g., block shape) can be obtained. By sintering this molded body, a porous anode body with one end of the anode lead embedded can also be formed.

[0077] (Step 1)

[0078] In the first step, a dielectric layer is formed on the anode body. The dielectric layer is formed by anodizing the anode body. Anodizing can be performed by known methods such as chemical conversion treatment. Chemical conversion treatment can be performed, for example, by immersing the anode body in a chemical conversion solution, allowing the chemical conversion solution to permeate the surface of the anode body, using the anode body as the anode, and applying a voltage between the anode body and the cathode immersed in the chemical conversion solution. As the chemical conversion solution, an aqueous solution of phosphoric acid is preferred, for example.

[0079] (Step 2)

[0080] The second step may include step a, which prepares the first treatment solution, and step b, which attaches the first treatment solution to the dielectric layer to form the first layer. In step b, for example, the first layer may be formed by immersing the anode body with the dielectric layer formed thereon in the first treatment solution and then drying it. In step b, the first treatment solution may also be formed by coating or dripping it onto the anode body with the dielectric layer formed thereon and then drying it.

[0081] The first processing solution may contain a self-doped polythiophene polymer (self-doped) having a conductivity of 2 S / cm or less. In this case, it is easy to prepare a dispersion of polythiophene polymer particles or a solution of polythiophene polymer as the first processing solution, and the dispersion (solution) of polythiophene polymer can easily penetrate into the pores of the porous portion. Alternatively, the first processing solution may also contain a polythiophene polymer composite (a composite of polythiophene polymer and a first dopant) having a conductivity of 2 S / cm or less. The substances described in the foregoing examples can be used as the polythiophene polymer and the first dopant. The first processing solution may also contain other components.

[0082] The first processing liquid can be, for example, a dispersion (or solution) of a polythiophene polymer, or a dispersion (or solution) of a polythiophene polymer complex with a first dopant. The first processing liquid can be obtained, for example, by oxidative polymerization of a polythiophene polymer precursor in a dispersion medium (or solvent). Examples of such precursors include monomers constituting the polythiophene polymer and / or oligomers linked with multiple monomers. The first processing liquid containing the polythiophene polymer complex can be obtained by oxidative polymerization of the polythiophene polymer precursor in a dispersion medium (or solvent) in the presence of the first dopant.

[0083] The conductivity of the first layer can be adjusted, for example, according to the polymerization conditions of the polythiophene polymer precursor (e.g., the type of polythiophene polymer precursor, oxidant, or catalyst), the type of the first dopant, etc.

[0084] Examples of dispersion media (or solvents) for the first treatment liquid include water, organic solvents, or mixtures thereof. Examples of organic solvents include monohydric alcohols (methanol, ethanol, propanol, etc.), polyhydric alcohols (ethylene glycol, glycerol, etc.), or aprotic polar solvents (N,N-dimethylformamide, dimethyl sulfoxide, acetonitrile, acetone, benzyl nitrile, etc.).

[0085] From the perspective of facilitating the penetration of the first treatment liquid into the pores of the porous material, the average particle size of the polythiophene-based polymer (or polythiophene-based polymer complex) particles dispersed in the first treatment liquid can be less than 100 nm or less than 50 nm. There is no particular limitation on the lower limit of the average particle size, for example, it can be greater than 5 nm. It should be noted that the average particle size referred to here is the median particle size (D50) in the volumetric particle size distribution. The average particle size of the polythiophene-based polymer (or polythiophene-based polymer complex) can be determined, for example, based on the particle size distribution obtained by dynamic light scattering (DLS). Specifically, using an aqueous dispersion of particles (first treatment liquid), the particle size distribution is measured on a volumetric basis using a dynamic light scattering particle size distribution measuring device (HORIBA, LB-550), and the median particle size (D50) is taken as the average particle size.

[0086] (Step 3)

[0087] In the third step, a precursor of a polypyrrole polymer is electrolytically polymerized on the first layer to form a second layer containing the polypyrrole polymer. Alternatively, in the presence of a second dopant, a precursor of a non-self-doped polypyrrole polymer can be electrolytically polymerized on the first layer to form a second layer containing both the polypyrrole polymer and the second dopant.

[0088] The second layer is formed by electrolytic polymerization using a second processing solution. The second layer is formed, for example, by immersing an anode having a dielectric layer and a first layer formed thereon in the second processing solution, and using the first layer as an electrode powered from a supply electrode. The second processing solution, for example, contains a precursor of a polypyrrole polymer, a second dopant, and a dispersion medium (or solvent).

[0089] The first layer has low electrical conductivity, which can sometimes lead to large overvoltages during electrolytic polymerization. This can sometimes affect the formation of the second layer. To uniformly form a high-quality second layer on the low-conductivity first layer, it is preferable to flow a small current through the first layer and perform electrolytic polymerization.

[0090] The substances described above can be used as both the polypyrrole polymer and the second dopant. Examples of precursors for the polypyrrole polymer include monomers constituting the polypyrrole polymer and / or oligomers linked with multiple monomers. The substances described in the first processing solution can be used as the dispersion medium (or solvent). The second processing solution may also contain other components.

[0091] (The process of forming the cathode lead-out layer)

[0092] In this process, a cathode lead-out layer is formed by sequentially stacking a carbon layer and a silver paste layer on the second solid electrolyte layer formed in the third process. By forming the cathode lead-out layer, a capacitor element can be obtained.

[0093] It should be noted that a conductive adhesive layer is disposed on the surface of the cathode lead-out layer, through which one end of the cathode terminal is electrically connected to the capacitor element. The cathode terminal can be any electrode terminal used in electrolytic capacitors without particular limitation; for example, a terminal known as a lead frame can also be used.

[0094] (The process of sealing capacitor elements with resin sealing material)

[0095] The formed capacitor element, for example, is sealed with a portion of both the anode and cathode terminals using a resin material. This sealing process forms a resin sealing material. Preferably, the resin material is a thermosetting resin (such as epoxy resin) or a resin composition. It should be noted that the resin sealing material comprises a cured product of the thermosetting resin or resin composition.

[0096] [Example]

[0097] The present invention will now be described in detail based on embodiments and comparative examples, but the present invention is not limited to the following embodiments.

[0098] Examples 1-5 and Comparative Examples 1-2

[0099] (The process of forming a dielectric layer on the surface of the anode body)

[0100] As the anode body, a tantalum sintered body (porous body) is prepared to embed a portion of the anode lead. The tantalum sintered body is cuboid, and the anode lead is embedded from one end face of the cuboid. For the anode body, anodizing is performed in an aqueous phosphoric acid solution to form a dielectric layer containing tantalum oxide (Ta2O5) on the surface of the anode body.

[0101] (The process of forming the first layer)

[0102] As the first conductive polymer, an aqueous dispersion (first treatment solution) containing a self-doped polythiophene polymer having the conductivity shown in Table 1 is prepared (step a). The concentration of the polythiophene polymer in the first treatment solution is 4% by mass. The polythiophene polymer particles are very small particles (particle size less than 1 nm) that are difficult to measure using the DLS method. As the self-doped polythiophene polymer, PEDOT with sulfonic acid groups directly bonded to the PEDOT backbone is used. An anode body with a dielectric layer formed is immersed in the first treatment solution and dried to form the first layer (step b).

[0103] (The process of forming the second layer)

[0104] Prepare an aqueous dispersion (second treatment solution) containing pyrrole and a dopant (a sulfonate with a naphthalene skeleton). It should be noted that the concentration of pyrrole in the second treatment solution can be appropriately selected, for example, in the range of 1 to 6% by mass, and the concentration of the dopant in the second treatment solution can be appropriately selected, for example, in the range of 3 to 12% by mass.

[0105] An anode body with a dielectric layer and a first layer is immersed in a second treatment solution, and pyrrole is electrolytically polymerized using the first layer as an electrode to form a second layer containing polypyrrole (conductivity 60 S / cm).

[0106] Thus, a solid electrolyte layer consisting of a first layer and a second layer is formed. The thickness of the first layer, T1, is 5 nm. The thickness of the second layer, T2, is 100 nm.

[0107] (The process of forming the cathode lead-out layer)

[0108] A dispersion of graphite particles in water is coated onto the surface of a solid electrolyte layer, and then dried to form a carbon layer. Next, a silver paste containing silver particles and a binder resin (epoxy resin) is coated onto the surface of the carbon layer, and the binder resin is cured by heating to form a silver paste layer. Thus, a cathode lead-out layer consisting of a carbon layer and a silver paste layer is formed. This yields a capacitor element.

[0109] (Process for sealing capacitor components)

[0110] An anode terminal (anode lead frame) is soldered onto the anode lead wire. The cathode terminal (cathode lead frame) is connected to the cathode lead layer using a conductive adhesive. The capacitor element is then sealed with a resin sealant. This process produces an electrolytic capacitor.

[0111] In the process of forming the first layer described above, self-doped polythiophene polymers with different conductivity were used as the first conductive polymer contained in the first processing solution to change the conductivity of the first layer to the values ​​shown in Table 1, and electrolytic capacitors were fabricated accordingly. In Table 1, A1 to A5 represent the electrolytic capacitors of Examples 1 to 5. B1 to B2 represent the electrolytic capacitors of Comparative Examples 1 to 2.

[0112] Comparative Example 3

[0113] In the process of forming the first layer, a first processing solution containing a self-doped polyaniline-based polymer (conductivity 0.1 S / cm) was used as the first conductive polymer. The anode body with the dielectric layer formed was immersed in the first processing solution and dried to form the first layer containing the polyaniline-based polymer. The self-doped polyaniline-based polymer used was polyaniline having sulfonic acid groups directly bonded to the polyaniline backbone. Except as described above, the electrolytic capacitor B3 of Comparative Example 3 was fabricated in the same manner as in Example 1.

[0114] [evaluate]

[0115] For the electrolytic capacitors of the above-described embodiments and comparative examples, the initial ESR (mΩ) was measured at a frequency of 100 kHz using a 4-terminal LCR meter at an environment of 20°C. Additionally, the capacitance (μF) was measured at a frequency of 120 Hz. Furthermore, the current flowing through the electrolytic capacitor was measured when the rated voltage was maintained for 40 seconds, and its value was determined as the leakage current. The evaluation results are shown in Table 1.

[0116] It should be noted that in Table 1, the ESR value represents a relative value when the ESR value of electrolytic capacitor A5 is set to 100. In Table 1, the capacitance of electrolytic capacitor A5 is set to 100%. Values ​​greater than 90% of the capacitance of electrolytic capacitor A5 are indicated by ○, and values ​​less than 90% are indicated by ×. In Table 1, leakage current below 100μA is indicated by 〇, and leakage current greater than 100μA is indicated by ×.

[0117] [Table 1]

[0118]

[0119] Electrolytic capacitors A1 to A5, whose first layer contains a polythiophene polymer and has a conductivity of 2 S / cm or less, exhibited lower ESR and lower leakage current than electrolytic capacitors B1 to B3. Electrolytic capacitors A2 to A5, whose first layer contains a polythiophene polymer and has a conductivity of 0.1 S / cm or more but less than 2 S / cm, exhibited both low ESR and high capacitance.

[0120] In electrolytic capacitors B1 to B2, where the conductivity of the first layer, which contains a polythiophene polymer, is greater than 2 S / cm, the ESR and leakage current increase. This is attributed to the difficulty in insulating the first layer due to its higher conductivity (greater than 2 S / cm). In electrolytic capacitor B3, the conductivity of the first layer is less than 2 S / cm, but the ESR increases because a polyaniline polymer film is formed as the first layer.

[0121] Industrial availability

[0122] The electrolytic capacitors involved in this invention are suitable for applications requiring low ESR.

[0123] Although the invention has been described in conjunction with presently preferred embodiments, this disclosure should not be interpreted as limiting. Various modifications and alterations will be readily apparent to those skilled in the art upon reading the foregoing disclosure. Therefore, the appended claims should be construed as encompassing all modifications and alterations without departing from the true spirit and scope of the invention.

[0124] Explanation of reference numerals in the attached figures

[0125] 1: Electrolytic capacitor; 2: Capacitor element; 3: Resin sealing material; 4: Anode terminal; 4S: Main surface of anode terminal; 5: Cathode terminal; 5S: Main surface of cathode terminal; 6: Anode body; 7: Dielectric layer; 8: Cathode portion; 9: Solid electrolyte layer; 9a: First layer; 9b: Second layer; 10: Cathode lead-out layer; 11: Carbon layer; 12: Silver paste layer; 13: Separation layer; 14: Adhesive layer.

Claims

1. An electrolytic capacitor comprising: Anode body, The dielectric layer covering the anode body, The first solid electrolyte layer covering the dielectric layer, and A second solid electrolyte layer covering the first solid electrolyte layer, The first solid electrolyte layer comprises a first conductive polymer with polythiophene as its basic framework. The second solid electrolyte layer comprises a second conductive polymer with polypyrrole as its basic framework. The conductivity of the first solid electrolyte layer is below 2 S / cm. The conductivity of the second solid electrolyte layer is higher than that of the first solid electrolyte layer.

2. The electrolytic capacitor according to claim 1, wherein, The conductivity of the first solid electrolyte layer is greater than 0.1 S / cm and less than 0.5 S / cm.

3. The electrolytic capacitor according to claim 1 or 2, wherein, The thickness of the first solid electrolyte layer is less than 10 nm.

4. The electrolytic capacitor according to claim 1 or 2, wherein, The thickness of the second solid electrolyte layer is greater than 50 nm and less than 100 nm.

5. The electrolytic capacitor according to claim 1 or 2, wherein, The conductivity of the second solid electrolyte layer is above 30 S / cm and below 300 S / cm.

6. The electrolytic capacitor according to claim 1 or 2, wherein, The first solid electrolyte layer comprises a self-doped first conductive polymer having a conductivity of less than 2 S / cm.

7. The electrolytic capacitor according to claim 1 or 2, wherein, The second solid electrolyte layer comprises the second conductive polymer that is not self-doped.

8. A method for manufacturing an electrolytic capacitor, comprising: The first step is to prepare an anode body with a dielectric layer. In the second step, a first solid electrolyte layer comprising a first conductive polymer with polythiophene as its basic framework is formed on the dielectric layer; and In the third step, a precursor of a second conductive polymer with polypyrrole as its basic framework is electrolytically polymerized on the first solid electrolyte layer to form a second solid electrolyte layer containing the second conductive polymer. The conductivity of the first solid electrolyte layer is below 2 S / cm. The conductivity of the second solid electrolyte layer is higher than that of the first solid electrolyte layer.

9. The method for manufacturing an electrolytic capacitor according to claim 8, wherein, The second step includes the following steps: The process of preparing a first treatment solution comprising a self-doped first conductive polymer having a conductivity of less than 2 S / cm: and, The process of attaching the first treatment liquid to the dielectric layer to form the first solid electrolyte layer containing the first conductive polymer.

Citation Information

Patent Citations

  • Solid electrolytic capacitor

    JP2008118060A

  • Solid electrolytic capacitor and method of manufacturing the same

    JP2011192688A